Exogenous arachidonic acid mediates permeability of human brain microvessel endothelial cells through prostaglandin E2 activation of EP3 and EP4 receptors. (27th April 2015) - Dalvi, Siddhartha; Nguyen, Hieu H.; On, Ngoc; Mitchell, Ryan W.; Aukema, Harold M.; Miller, Donald W.; Hatch, Grant M.
Abstract: The blood–brain barrier, formed by microvessel endothelial cells, is the restrictive barrier between the brain parenchyma and the circulating blood. Arachidonic acid (ARA; 5, 8, 11, 14‐ cis ‐eicosatetraenoic acid) is a conditionally essential polyunsaturated fatty acid [20:4( n  − 6)] and is a major constituent of brain lipids. The current study examined the transport processes for ARA in confluent monolayers of human brain microvascular endothelial cells (HBMEC). Addition of radioactive ARA to the apical compartment of HBMEC cultured on Transwell ® inserts resulted in rapid incorporation of radioactivity into the basolateral medium. Knock down of fatty acid transport proteins did not alter ARA passage into the basolateral medium as a result of the rapid generation of prostaglandin E2 (PGE2 ), an eicosanoid known to facilitate opening of the blood–brain barrier. Permeability following ARA or PGE2 exposure was confirmed by an increased movement of fluorescein‐labeled dextran from apical to basolateral medium. ARA‐mediated permeability was attenuated by specific cyclooxygenase‐2 inhibitors. EP3 and EP4 receptor antagonists attenuated the ARA‐mediated permeability of HBMEC. The results indicate that ARA increases permeability of HBMEC monolayers likely via increased production of PGE2 which acts upon EP3 and EP4 receptors to mediate permeability. These observations may explain the rapid influx of ARA into the brain previously observed upon plasma infusion with ARA. The blood–brain barrier, formed by microvessel endothelial cells, is a restrictive barrier between the brain parenchyma and the circulating blood. Radiolabeled arachidonic acid (ARA) movement across, and monolayer permeability in the presence of ARA, was examined in confluent monolayers of primary human brain microvessel endothelial cells (HBMECs) cultured on Transwell ® plates. Incubation of HBMECs with ARA resulted in a rapid increase in HBMEC monolayer permeability. The mechanism was mediated, in part, through increased prostaglandin E2 production from ARA which acted upon EP3 and EP4 receptors to increase HBMEC monolayer permeability. Abstract : The blood–brain barrier, formed by microvessel endothelial cells, is a restrictive barrier between the brain parenchyma and the circulating blood. Radiolabeled arachidonic acid (ARA) movement across, and monolayer permeability in the presence of ARA, was examined in confluent monolayers of primary human brain microvessel endothelial cells (HBMECs) cultured on Transwell ® plates. Incubation of HBMECs with ARA resulted in a rapid increase in HBMEC monolayer permeability. The mechanism was mediated, in part, through increased prostaglandin E2 production from ARA which acted upon EP3 and EP4 receptors to increase HBMEC monolayer permeability. Read theEditorial Highlight for this article on page845 .